Consequences of Non-compliance with the Constitutional Court Decision in Judicial Review of the UUD 1945 - Pitriyantini, Putu Eka; Astariyani, Ni Luh Gede (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 10 No 4 (2021), 2021)
This writing aimed to examine the causes of non-compliance with the implementation of the Constitutional Court Decision as well as analyze and axamine the consequence of non-compliance with the decisions of the Constitutional Court in Reviewing Laws and Constitutional Court Decisions. This writing was normative legal research using statutory approach, conceptual approach and historical approach. The study indicated that there are several causes leading to non-compliance with the implementation of the Constitutional Court Decisions; among others are the sectoral ego of state institutions that causes reluctance to implement the Constitutional Court decisions, the Constitutional Court which does not have an executive body, the void of legal norms, the connection with state institutions that are obliged to follow up on the Constitutional Court decisions, and the interpretation of the final meaning attached to the Constitutional Court decisions. These things have resulted in injustice to the petitioners and citizen whose constitutional rights have been violated by policies of government.